Practical Work in Science Education: Study of Different Contexts of Pedagogic Practice - Ferreira, Sílvia; Morais, Ana M. (Research in science education (Australasian Science Education Research Association), 2020)
The study investigates differentiated teaching practices of practical work in distinct social contexts and with different experienced teachers, at the level of the Portuguese high school science education. Four teaching practices were analysed in terms of the level of complexity of both scientific knowledge and cognitive skills and in terms of their structural and interactional characteristics, i.e. the nature of the sociological relations between subjects and discourses. The study is epistemologically, psychologically and sociologically grounded, particularly on Bernstein’s theory of pedagogic discourse. Four teachers and their 10th grade Biology and Geology classes of four distinct public schools were selected. The results showed that the social context of the school together with teachers’ academic qualification and professional development seems to influence science teachers’ practices in practical work contexts. Schools placed in the lower levels of national external assessment and also whose students came from social sectors with fewer resources showed to have teachers’ practices characterised by lower levels of complexity of both scientific knowledge and cognitive skills, a valuing of the horizontal discourse and implicit evaluation criteria. The conceptualization and procedures of the study followed a rigorous approach that may be transferred to other studies.